Two-dimensional video analysis of the overhead squat: a preliminary study - Antônio Ribeiro Neto; Lucimara Ferreira Magalhães; Rafael Rosano Gotti Alves; Gladson Ricardo Flor Bertolini; Daniel Ferreira Moreira Lobato; Dernival Bertoncello (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of this study was to identify changes in the pattern of movement during performance of the overhead squat, as well as possible differences between the sexes, during a protocol of an extreme conditioning program. The subjects were eleven men (28.6 ± 4.5 years, 85.1 ± 8.4 kg, 1.80 ± 0.07 m, and 13.8 ± 7.7 months of practice) and eleven women (30.5 ± 4.8 years, 68.2 ± 10.36 kg, 1.70 ± 0.05 m, and 20.3 ± 17.01 months of practice), all of whom were extreme conditioning program practitioners. The protocol chosen for the training was the “Nautical Nancy”, which consisted of 5 rounds of 15 overhead squats and 400 meters of rowing. During the exercise, an analysis was performed in which the shoulder, knee, and hip flexion angles were analyzed in the first and last rounds. For men, there were increases of the shoulder and hip flexion angles, while the women showed increase of the shoulder flexion angle and decrease of the knee flexion angle. Changes in technique occurred due to the attempt at self-preservation on the part of the practitioners, when exposed to the protocol, which could lead to increased risk of injury.